Residual stress distributions in arc, laser and electron-beam welds in 30 mm thick SA508 steel: A cross-process comparison. (May 2018) - Balakrishnan, J.; Vasileiou, A.N.; Francis, J.A.; Smith, M.C.; Roy, M.J.; Callaghan, M.D.; Irvine, N.M.
Abstract: Safety-critical pressure vessels in pressurised water reactors (PWRs), such as the reactor pressure vessel and the steam generators, have been fabricated using arc welding processes for several decades. However, recent interest in nuclear new-build programmes has stimulated interest in reassessing the technologies that are available for the welding of these components. For example, considerable effort has been directed at the development of reduced-pressure electron beam (RPEB) welding, owing to the substantial productivity gains it would offer, while developmental work has also been carried out on multipass narrow-gap laser welding (NGLW). In this work we assess the effects that two current technologies, and two candidate technologies for future build programmes, are likely to have on the generation of residual stresses within critical nuclear components. Single-sided welds were manufactured in 30 mm thick plates of SA508 steel, using four welding processes: gas-tungsten arc welding (GTAW), submerged-arc welding (SAW), multipass NGLW and RPEB welding. The residual stress distributions for each type of weld have been measured both in the as-welded condition and after post-weld heat treatment, using neutron diffraction and the contour method. The results are compared and discussed. Highlights: Systematic comparison of residual stress distributions for four different welding processes. Welding processes include current technologies for nuclear pressure vessels and candidates for future application. Residual stresses measured with neutron diffraction and the contour method. Measurements were made in the as-welded condition and after post-weld heat treatment. Peak tensile residual stresses were similar in magnitude for each welding process, but the stress distributions differed.